Regeneration of the historic waterfront of world heritage sites in Malaysia – the case of Penang and Melaka - Shamsuddin, Shuhana; Sulaiman, Ahmad Bashri; Alias, Nor Syahida Alfath; Abdul Latip, Nurul Syala; Ujang, Norsidah; Chelliapan, Shreesivadan; Azlan, Nurul Azreen (2010)
Introduction. "Waterfront‟ in the context of towns and cities deals with the areas that are in direct contact with the water bodies. Malaysia‟s Department of Drainage and Irrigation defines the waterfront development as area within 50m or two lots of building from the banks (JPS, 2003)where the water is visually noticeable. An example of an edge as suggested by Lynch (1960) as one of the five elements that people use to structure the urban form. Paumier (2004) stated that waterfront areas as a vital assets where changes in transportation and economics have made land and buildings available for reuse. Waterfront regeneration is gaining momentum in urban regeneration that many cities around the world needed to bring back the abandoned or underutilised inner city harbours as a place to work, live and play. Many opportunities for successful redevelopment had emerged in rehabilitation of urban waterfront areas where the present trend sees recreation and tourism as a catalyst for redevelopment (Craig-Smith and Fagence, 1995). In the United States, Japan, United Kingdom, Caribbean and Australia, a set of principles and guidelines were used for the achievement of sustainable urban environments to be implemented.